Protection of women from domestic violence act, 2005 (act no. 43 of 2005) - Shree ram law house; Bare Act (Chandigarh Shree Ram Law house, 2024)
The protection of women from domestic violence act, 2005 (act no. 43 of 2005) with the protection of women from domestic violence rules, 2006 & the dowry prohibition act, 1961.
Keywords: Rrotection of Women; Domestic Violence Act